Privatization of community corrections - Latessa, Edward J. - (Criminology & public policy, 2019)
In this article, we examine the issue of privatization in the field of community corrections. Privatization can be found in all elements of community corrections, including treatment, education, housing, and supervision services. The private sector is also involved in the development of technology, like electronic monitoring devices, and material like assessments and curricula. Services are provided by both private for‐profit and nonprofit agencies. Although there are potential harms and benefits to privatization in community corrections, untangling the private industry from the provision of supervision and programming in the community would be a true challenge.